2020
DOI: 10.1111/2041-210x.13520
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised acoustic classification of individual gibbon females and the implications for passive acoustic monitoring

Abstract: Passive acoustic monitoring (PAM) has the potential to greatly improve our ability to monitor cryptic yet vocal animals. Advances in automated signal detection have increased the scope of PAM, but distinguishing between individuals—which is necessary for density estimation—remains a major challenge. When individual identity is known, supervised classification techniques can be used to distinguish between individuals. Supervised methods require labelled training data, whereas unsupervised techniques do not. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 95 publications
0
41
0
Order By: Relevance
“…Our study provides additional evidence regarding the utility of PAM and automatic acoustic detection as useful tools to study patterns of activity of primates across their diel activity cycle [22,23,45,46]. PAM coupled with automatic detection of calls allowed us to monitor larger areas for longer periods and gain new insight into the behavioral ecology of this species.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our study provides additional evidence regarding the utility of PAM and automatic acoustic detection as useful tools to study patterns of activity of primates across their diel activity cycle [22,23,45,46]. PAM coupled with automatic detection of calls allowed us to monitor larger areas for longer periods and gain new insight into the behavioral ecology of this species.…”
Section: Discussionmentioning
confidence: 86%
“…Emerging new technologies and techniques, such as passive acoustic monitoring (PAM) and automatic acoustic detection of calls [20][21][22], greatly facilitate studying soundproducing animals at night and have the potential to advance both behavioral ecology and conservation practices [23][24][25]. Recently, researchers have used PAM and automatic classifiers to decipher diel and annual vocal cycles of black-and-gold howlers and mantled howlers [5,26] and expanded upon the number of acoustic features analyzed for black howlers (Alouatta pigra) and mantled howlers [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the number of wolves present in the recordings could be determined from their howls and the individuality information is sufficient for supervised population estimation through CMR techniques 7 , 25 , 27 , 30 . Therefore, wolves recorded in one location can be acoustically recaptured at another location, and we can identify them individually.…”
Section: Discussionmentioning
confidence: 92%
“…There are two ways to identify individual wolves or packs—supervised clustering and unsupervised clustering. While supervised clustering requires a set of known training data and cluster validation is straightforward, unsupervised clustering requires ground-truthing before it can be used to monitor populations at a survey level and does not allow individual level CMR or tracking 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation